Differentiation of Learning Styles In The Al-Qur’an: Analytical Study of Learning Stories in the Al-Quran - Makhzuniyah, Minhah; Fatimah, Misyka Nuri (Fakultas Tarbiyah, Institut PTIQ Jakarta, 2024)
The development of learning strategy continuous to be main topic of discussion in learning process. All of the implementer and the stakeholders want the change that leads to better learning. The term differentiation of learning style comes up to highlight that every human has different learning style that impacts to the choice of learning strategy implemented. This research used qualitative approach which focused on how al-Qur’an has different learning styles as well that are found in some stories written in al-Quran. This research used library research that would investigate about al-Quran that delivers about learning process and educational knowledge. The findings of this research indicated that from three stories taken from al-Quran gave three different descriptions of learning styles. How Qobil story showed learning process with visual learning style. Then story about Luqmanul Hakim and his son revealed auditory learning style, while Ibrohim and Ismail’s story presented kinesthetic learning style. By seeing this result, it indicated that al-Quran has described the difference of learning style in every story that proved the difference of learning styles have existed since ancient time in accordance with the potency and the need of learning process. Those three stories are able to develop in today learning process.